2018
DOI: 10.1186/s41200-018-0136-3
|View full text |Cite
|
Sign up to set email alerts
|

Second survey of heterobranch sea slugs (Mollusca, Gastropoda, Heterobranchia) from Bunaken National Park, North Sulawesi, Indonesia - how much do we know after 12 years?

Abstract: Background: Bunaken National Park (BNP) is one of the most famous marine national parks in Indonesia with an extraordinary diversity in marine life forms. However, this diversity is threatened by an increasing population on the islands, ongoing destructive fishing techniques and lately by an increase in tourism. Protecting and managing the future use of BNP resources will require the assessment of both, local marine biodiversity through monitoring efforts and the identification and subsequent reduction of any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 19 publications
(16 reference statements)
5
40
2
7
Order By: Relevance
“…In order to monitor potential damage to the environment around Sangihe, irrespective of its original cause, we have started with a first survey in 2016, focusing on marine Heterobranchia. Here we present the first results from this collecting period and compare our results with former studies in Bunaken National Park [13,14] and other areas in and around Indonesia.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In order to monitor potential damage to the environment around Sangihe, irrespective of its original cause, we have started with a first survey in 2016, focusing on marine Heterobranchia. Here we present the first results from this collecting period and compare our results with former studies in Bunaken National Park [13,14] and other areas in and around Indonesia.…”
Section: Introductionsupporting
confidence: 55%
“…This spectrum covers nearly all sessile organisms (algae, poriferans, cnidarians, ascidians, bryozoans, tunicates). Thus, this group was already used for monitoring coral reef diversity in North Sulawesi [12][13][14][15]. Because marine Heterobranchs are also very attractive to tourists, additional data are and will be available through citizen science due to documentation in websites or personal information and provision of images on personal bases.…”
Section: Introductionmentioning
confidence: 99%
“…The identification process is carried out by comparing the morphological details of each specimen from the photograph with material source like books and journals, and also got its taxon verified by the World Register of Marine Species' website [18]. The fishes identifications are mainly compared to identification books [19][20][21], while the sea slugs are compared to various sources like book [22], scientific publications [23][24][25][26][27], and additionally the Bill Rudman's Sea Slug Forum [28]. The polyclad flatworms identified by comparing to journals [29][30][31][32], while the arthropods (crustacean) identifed by comparing to book [33].…”
Section: Methodsmentioning
confidence: 99%
“…During various species diversity studies in Bunaken National Park, North Sulawesi, Indonesia Kaligis et al 2018), four undescribed species of Noumeaella Risbec, 1937 were recorded. Edmunds (1970) postulated a close relationship between Noumeaella, Palisa Edmunds, 1964 andMoridilla Bergh, 1888, based on similarities of rhinophores, foot tentacles, cerata shape and radula morphology.…”
Section: Introductionmentioning
confidence: 99%
“…A barcoding approach of the Bunaken material from the studies of Eisenbarth et al (2018) and Kaligis et al (2018) revealed that two of the therein mentioned Noumeaella species actually group with the genus Moridilla. This corroborates the difficulty in assigning specimens correctly to the genera mentioned.…”
Section: Introductionmentioning
confidence: 99%